EnergyPlus as a forensic tool: Thermal reconstruction of a crime scene using calibrated simulation. (August 2014) - Brown, Nathan; Ubbelohde, M Susan; Loisos, George; Philip, Santosh; Santiago, Ibone
This study utilized energy simulation in support of a forensic pathology time-of-death analysis for a corpse discovered in a single-family residence two years prior to the study. In order to produce an accurate estimate of the interior temperature profile at the time of death, a thermal model was constructed using EnergyPlus and calibrated using environmental monitoring data from the site. The calibration methods used in the study draw from several precedents and are presented in detail. The thermal model was able to predict the temperature in the room of interest within 1.4°C (2.5°F) with 90% confidence. This model was then altered to account for known differences between the monitoring period and the period of interest, and used to predict what the temperature profile had been at the time of death. This study adds to a small body of work that compares simulated to measured performance data for unconditioned spaces, which should have a growing relevance as building energy performance simulation tools are used to model passive strategies.